Visual Religion dan Gerakan Hijrah: Analisis Dakwah Film Ketika Mas Gagah Pergi di Era Digital - Ramidi (Mudabbir: Jurnal Manajemen Dakwah, 2025)
This article departs from the problem of how the youth da'wah movement is realized through new media, and how the representation of hijrah is depicted in the film Ketika Mas Gagah Pergi by Helvy Tiana Rosa. This study uses a qualitative approach with a content analysis method for films, as well as examines various supporting literature related to youth da'wah, new media, and Islamic popular culture in Indonesia. The analysis shows that the film Ketika Mas Gagah Pergi represents hijrah as a process of spiritual and social transformation of urban youth from hedonistic life to meaningful religiosity. Da'wah in this film is present through emotional and visual narratives that are close to the experiences of young people, not through normative lectures. In addition, the film Ketika Mas Gagah Pergi functions not only as a medium for da'wah, but also as a place for the representation of the identity and spirituality of young Muslims. However, the film also shows ambivalence in the representation of hijrah between substantive and symbolic transformations so that it demands critical reflection on the commodification of religion in the space of popular culture.